The Super Anti-Browning Effect of High-Oxygen Pretreatment Combined with Cod Peptides on Fresh-Cut Potatoes During Storage - Jiaxuan Zheng; Yishan Jiang; Aiguang Li; Mengfei Peng; Ting Wang; Runlei Kou; Ji Kang; Xia Liu (Foods)
Enzymatic browning poses a formidable obstacle to the commercial sustainability of fresh-cut potatoes. Although the synergistic effects of bio-inductive technologies with natural compounds in anti-browning strategies have been observed, their full potential remains underexplored. To fulfill the demand for synergistic approaches in real-world applications, this research elucidates the complementary effects of short-term high-oxygen (HO, 80%) treatment of whole tubers in conjunction with cod peptides (CP, 0.1%) applied to fresh-cut potato slices in mitigating browning. The results demonstrated that the combined treatment (HO + CP) showed superior anti-browning efficacy compared to single treatments (HO or CP) and the untreated group (control). Specifically, peroxidase (POD) and polyphenol oxidase (PPO) activities were suppressed by 55.7% and 35.1%, respectively, under the synergistic treatment compared with the control after 8 days of storage. Meanwhile, increases in the activities of catalase (CAT), superoxide dismutase (SOD), and phenylalanine ammonia-lyase (PAL), along with an approximately 117% increase in total phenolic content, were noted with synergistic treatment. Furthermore, the combined treatment reduced malondialdehyde (MDA) accumulation by 17.5% on day 8. This effect may be attributed to enhanced antioxidant capacity and the preservation of membrane integrity. In summary, this novel strategy provides a practical synergistic solution for the control of enzymatic browning in fresh-cut potatoes.